Long-term kappa-carrageenan consumption leads to moderate metabolic disorder by blocking insulin binding. (March 2021) - Zhou, Jiawei; Wang, Feng; Chen, Juanjuan; Yang, Rui; Chen, Yuhao; Gu, Denghui; Niu, Tingting; Luo, Qijun; Yan, Xiaojun; Chen, Haimin; Wu, Wei
Graphical abstract: Highlights: κ-Carrageenan, a widely used polysaccharide interferes with the binding of insulin to receptor. κ-Carrageenan causes non-diabetic less weight gain by impairing glucose metabolism in mice. κ-Carrageenan inhibits the insulin PI3K/AKT signaling pathway. Abstract: Carrageenan (CGN) is a common food additive, and questions have been raised regarding its safety for human consumption. The purpose of this study was to investigate the impact of κ-CGN on glucose intolerance and insulin resistance from the perspective that κ-CGN may interfere with insulin receptor function and affect insulin sensitivity and signaling, thereby leading to body weight loss. The health effects of κ-CGN on C57BL/6 mice were assessed over a 90-d period by monitoring changes in body weight, glucose tolerance, insulin tolerance, fasting glucose and insulin levels, and expression of insulin-pathway-related proteins. Furthermore, HepG2 cells were used to detect the binding of κ-CGN on insulin receptor and measure its effect on downstream signal transduction. In mice, κ-CGN treatment reduced weight gain without affecting food intake. Glucose and insulin tolerance tests revealed that κ-CGN treatment increased blood glucose levels and glycosylated hemoglobin levels, while hepatic and muscle glycogen levels were decreased, suggesting that κ-CGN affected glucose metabolism in mice. Interestingly, κ-CGN treatment did not cause typical diabetic symptoms in mice, as indicated by low levels of fasting and postprandial blood glucose, in addition to normal pancreatic tissue and insulin secretion. The binding studies revealed that κ-CGN could competitively bind to the insulin receptor with FITC-insulin and thereby disrupt PI3K and Akt activation, thus suppressing expression of glucose transporters and glycogen synthase. In summary, this study revealed that κ-CGN reduced weight gain without affecting food intake, but impaired glucose metabolism in mice by interfering with insulin binding to receptors, thereby affecting the sensitivity of insulin and inhibiting the insulin PI3K/AKT signaling pathway, causing non-diabetic weight gain reduction.